2009
DOI: 10.1111/j.1945-5100.2009.tb01188.x
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Wild 2 dust fine structure: Comparison of Stardust aluminum foil craters to the three‐dimensional shape of experimental impacts by artificial aggregate particles and meteorite powders

Abstract: available online at Abstract-New experimental results show that Stardust crater morphology is consistent with interpretation of many larger Wild 2 dust grains being aggregates, albeit most of low porosity and therefore relatively high density. The majority of large Stardust grains (i.e. those carrying most of the cometary dust mass) probably had density of 2.4 g cm −3 (similar to soda-lime glass used in earlier calibration experiments) or greater, and porosity of 25% or less, akin to consolidated carbonaceous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 72 publications
3
51
2
Order By: Relevance
“…However, because Stardust foil surfaces present only a planar section through complex 3‐D, polygonal crystal shapes (flattened by rolling during foil fabrication) it is also not possible for us to make a simple judgement as to the proximity of a particular crater to all possibly significant grain boundaries (which may lie beneath). So far, we have found no evidence of a wider range of crater morphology in our smallest (∼500 nm) impactor shots; this is in contrast to the wide range of shape seen in the smaller Stardust craters (see below) which we have attributed to complex internal structures with Wild 2 dust grains (Kearsley et al. 2009).…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation
“…However, because Stardust foil surfaces present only a planar section through complex 3‐D, polygonal crystal shapes (flattened by rolling during foil fabrication) it is also not possible for us to make a simple judgement as to the proximity of a particular crater to all possibly significant grain boundaries (which may lie beneath). So far, we have found no evidence of a wider range of crater morphology in our smallest (∼500 nm) impactor shots; this is in contrast to the wide range of shape seen in the smaller Stardust craters (see below) which we have attributed to complex internal structures with Wild 2 dust grains (Kearsley et al. 2009).…”
Section: Resultscontrasting
confidence: 84%
“…(2008a) that such particles comprise a small proportion of the total cometary dust mass remains valid. Evidence from crater depth profiles (Kearsley et al. 2008a, 2008b, 2009) also indicates that the density of most of the larger particles was relatively high, and they should not be considered as highly porous, of low density, and hence low mass contributors.…”
Section: Discussionmentioning
confidence: 99%
“…Case II has a radius, bulk density and albedo of 130 m, 1000 kg m −3 and 0.04, respectively. If we assume the solid component (both the nucleus and the dust) to have specific density similar to that found for the dust particles of comet Wild 2, ∼3400 kg m −3 (Kearsley et al 2009), we can constrain the initial ice abundances for the thermal evolution calculations (see Prialnik et al 2008). These values are taken as 0.05 and 0.5 (with corresponding initial porosities of 0.01 and 0.3) for Case I and Case II, respectively.…”
Section: Thermal Modelmentioning
confidence: 99%
“…The two-stage light gas gun (LGG) is used to study impacts on materials commonly used on space vehicles [1][2][3] The Kent LGG shown in Fig. 1, fires small projectiles (micron to mm size) at speeds from 1 km/s to 8.4 km/s.…”
Section: Introductionmentioning
confidence: 99%